Evaluation of CTLA-4 Gene polymorphism SNP 49 G/ A Association with Diabetes Mellitus Type 1 in Egyptian Population - Al-shehmany, Ali Salim; A. El- Kafoury, Ahmad; A. Haroun, Medhat; M. Embaby , Amira (Iraqi Journal of Science, 2026)
The (CTLA-4) encodes of the T cell receptor involved in the control of T cellproliferation and mediates T cell apoptosis. The contribution of CTLA-4 genevariants to type 1 diabetes has been analyzed in several ethnic groups. In this study,the association of CTLA-4 +49 A/G polymorphism with type 1 diabetes wasinvestigated in Egyptian patients. Sixty type 1 diabetic patients (25 males and 35females) and 60 healthy individuals (33 males and 27 females) subjects formed thestudied populations. CTLA-4 A/G polymorphism at position 49 in exon 1 wasidentified using allele specific methods. Patient numbers with A/G, A/A and G/Ggenotypes were 45 (75.0 %), 6 (10.0 %) and 9 (15.0%) while in healthy controls,these were 48 (80.0%), 2 (3.3%) and 10 (16.7%), respectively. In conclusion, theresults of this study showed that CTLA-4 +49 A/G polymorphism were notassociated with susceptibility to type 1 diabetes in Egyptian population.